Selenium Supplementation and Crop Plant Tolerance to Metal/Metalloid Toxicity - Hasanuzzaman, Mirza; Nahar, Kamrun; García-Caparrós, Pedro; Parvin, Khursheda; Zulfiqar, Faisal; Ahmed, Naznin; Fujita, Masayuki (Frontiers in Plant Science, 2022)
Selenium (Se) supplementation can restrict metal uptake by roots and translocation to shoots which is one of the vital stress tolerance mechanisms. Selenium can also enhance cellular functions like membrane stability, mineral nutrition homeostasis, antioxidant response, photosynthesis and thus improve plant growth and development under metal/metalloid stress. Metal/metalloid toxicity decreases crop productivity and uptake of metal/metalloid through food chain causes health hazards. Selenium has been recognized as an element essential for the functioning of the human physiology and is a beneficial element for plants. Low concentrations of Se can mitigate metal/metalloid toxicity in plants and improves tolerance in various ways. Selenium stimulates the biosynthesis of hormones for remodeling the root architecture that decreases metal uptake. Growth enhancing function of Se has been reported in number of studies which is the outcome of improvement of various physiological features. Photosynthesis has been improved by Se supplementation under metal/metalloid stress due to prevention of pigment destruction, sustained enzymatic activity, improved stomatal function and photosystem activity. By modulating the antioxidant defense system Se mitigates oxidative stress. Selenium improves the yield and quality of plants. However, excessive concentration of Se exerts toxic effects on plants. This review presents the role of Se for improving plant tolerance to metal/metalloid stress.